Anthropometric differences and maximal aerobic power among men and women in racing-boat rowing - Larrinaga, B.; Río, X.; Coca, A.; Rodriguez-Alonso, M.; Arbillaga-Etxarri, A. (Archivos de medicina del deporte, 2023)
Anthropometric, mechanical and performance differences have been observed in rowing between rowers from the same club competing in different categories. Maximal aerobic power has been defined as one of the best predictors of rowing performance. The aim was to observe differences between male and female rowers in anthropometric, physiological and aerobic power data. Weight (P), height (T), fat percentage (G), sum of seven folds (S7) and absolute and relative watts (W) (W/kg) of 55 subjects were assessed. Of the 55 subjects, 38 were male (26.95 ±7.0 years) and 17 were female (24.82 ±6.8 years). Cohen`s d was used to calculate the effect size as standardised mean difference. In the results, sample means were obtained for the variables analysed in the different sexes (F: females and M: males). For F: [P: 77.25 (9.41) - T: 1.80 (0.07) - G: 12.77 (3.04) - S7: 72.23 (28.20) - W: 273.6 (52.88) - W/kg: 3.57 (0.67)] and for M: [P: 61.79 (6.85 - T: 1.67 (0.07) - G: 14.44 (2.47)- S7: 103.83 (28.64) - W: 171.35 (29.19) - W/kg: 2.78 (0.43)]. Finally, the results were as follows: P: 1.77 - T: 1.87 - G: 0.57 - S7: 1.11 - W: 2.17 - W/kg: 1.28. Showing significant differences and a large effect size between both sexes in all the variables analysed, except for the fat percentage variable